2013
DOI: 10.1021/ac402390q
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Recognition Analysis for Hepatotoxicity Induced by Acetaminophen Using Plasma and Urinary 1H NMR-Based Metabolomics in Humans

Abstract: Drug-induced liver injury (DILI) is currently an increasingly relevant health issue. However, available biomarkers do not reliably detect or quantify DILI risk. Therefore, the purpose of this study was to comparatively evaluate plasma and urinary biomarkers obtained from humans treated with acetaminophen (APAP) using a metabolomics approach and a proton nuclear magnetic resonance (NMR) platform. APAP (3 g/day, two 500 mg tablets every 8 h) was administered to 20 healthy Korean males (age, 20-29 years) for 7 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 43 publications
3
46
0
Order By: Relevance
“…For NMR analysis, urine samples were thawed at 0 1C and then centrifuged at 3000 rpm for 15 min. A 500-μL sample of urine was mixed with 200 μL of phosphate buffer in D 2 O (0.2 M Na 2 HPO 4 Á 12H 2 O/0.2 M NaH 2 PO 4 Á 2H 2 O, 81:19, v/v, pH 7.4), containing 0.015% TSP (used as chemical shift reference) (Carrola et al, 2010;Kim et al, 2013). After centrifugation at 13,000 rpm for 20 min, 600 μL of supernatant was transferred into 5-mm NMR tubes.…”
Section: Sample Collection and Preparationmentioning
confidence: 99%
“…For NMR analysis, urine samples were thawed at 0 1C and then centrifuged at 3000 rpm for 15 min. A 500-μL sample of urine was mixed with 200 μL of phosphate buffer in D 2 O (0.2 M Na 2 HPO 4 Á 12H 2 O/0.2 M NaH 2 PO 4 Á 2H 2 O, 81:19, v/v, pH 7.4), containing 0.015% TSP (used as chemical shift reference) (Carrola et al, 2010;Kim et al, 2013). After centrifugation at 13,000 rpm for 20 min, 600 μL of supernatant was transferred into 5-mm NMR tubes.…”
Section: Sample Collection and Preparationmentioning
confidence: 99%
“…Urine is proving to be an increasingly useful source of metabolites and protein biomarkers for detecting disease states in both adults and neonates, [4][5][6][7] as well as the effects of drugs and dietary intake on physiologic processes. [8][9][10] Best Practices 11 and Standard Operating Procedures [12][13][14][15][16] for routine processing and storing of biobank samples have been published.…”
mentioning
confidence: 99%
“…Metabolic profiling in urine has also been performed in search for metabolites associated with DILI. Healthy volunteers administered non-toxic levels of APAP presented both urine and plasma metabolic alterations when comparing pre- and post-dosing samples, which were more sensitive than changes in serum biochemical parameter over the study period (Kim et al, 2013). It should be pointed out that while many metabolic studies to date coincide in detecting variations in endogenous metabolites, the identified metabolites often vary between studies.…”
Section: New Potential Biomarkers In Dilimentioning
confidence: 99%